Impact of inverse plasma filtration on complement activation in porcine blood - Haltern, Claudia; Kirschfink, Michael; Rossaint, Rolf; Unger, Juliane K. (Artificial organs, 2005)
During extracorporeal circulation, activation of the complement system as a bioincompatibility reaction upon contact with artificial surfaces is well known. This may induce adverse effects for the patient as well as for the bioreactor when using a hybrid liver support system. At present, the achievable clearance rates in hybrid liver support systems are restricted by the limitations of blood flow through the capillaries of the plasma filter. In order to enhance clearance rates it is desirable to develop a high-flow plasma separation unit in which the activation of the complement system is as low as possible. Conventional plasma filters operating in normal and in inverse (blood flow around the capillaries and the capillary lumen serving as plasma compartment) modes were investigated applying an in vitro circuit (n = 4 in each group). For this purpose heparinized porcine blood was used. Complement activation was measured as generation of the soluble membrane attack complex, SC5b-9. With a normal flow mode the maximum achievable filtration rates varied from 25 to 40 mL/min, whereas the maximal filtration rates with an inverse flow mode varied from 40 to 100 mL/min. While these values were significantly higher than those with regularly operating plasma filters, there was no significant difference between normal and inverse mode in the production of SC5b-9. We conclude that the outer surface of the investigated conventional plasma filtration membranes is suitable for an inverse mode and does not lead to an excessive activation of the complement system upon dynamic blood contact. Thus, the inversion of the blood and the plasma compartments may be a possible way forward in the development of a high-flow plasma separation filter.
First published: 22 March 2005
Gesehen am 15.02.2021